DISCUSSING METHODOLOGICAL ASPECTS OF TEACHING AND LEARNING IN EDUCATIONAL SERVICE SPECIALIST FOR STUDENTS WITH DEAFNESS - Flavia Roldan Viana; Adriana Leite Limaverde Gomes (Universidade Estadual Paulista Júlio de Mesquita Filho, 2017)
This article aims to highlight the educational practices for students with deafness in the Specialist Educational Attendance - AEE. In the teaching practice, the main difficulties encountered in the process of school inclusion of people with deafness refer, for example, the lack of sign language and the lack of adequate methodological strategies to a school that respects the uniqueness of the deaf individual. In this scenario, the AEE comes in order to create and improve the conditions for learning and school education for all. This is a theoretical essay based on a critical review of the literature. Discussions on the teaching practices for students with hearing loss in the AEE will be presented focusing on elements that enhance the view of the actual conditions of educating deaf, motivated by the belief in their potential for development and learning. It is necessary to strengthen the functioning of the AEE but in contrast to a use driven by fads and/or the desire of speeches to be only an inclusive practice. Keywords: Deafness Students. Teaching and learning. Specialized educational assistance.